Microwave heating of dry and water saturated basalt, granite and sandstone. (25th February 2010) - Peinsitt, Thomas; Kuchar, Friedemar; Hartlieb, Philipp; Moser, Peter; Kargl, Hubert; Restner, Uwe; Sifferlinger, Nikolaus
The heating of rocks with low to medium microwave absorption strength and its dependence on the water content is investigated in a 3 kW microwave oven at 2.45 GHz. Sandstone, granite, and basalt are chosen as the rock materials where basalt has the relatively highest absorption strength in the dry state. The effect of the microwaves at low energy input is investigated by measurements of the uniaxial compressive strength and the ultrasound velocity. The latter is found to be more reliable and is used for deducing trends caused by microwave irradiation. The largest effect due to the water content is observed in sandstone. At high energy input in basalt the interior melts and the samples break.